THE COMPLEXITIES OF TRANSLATING INTERNATIONAL TREATIES AND AGREEMENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the complexities involved in translating international treaties and agreements, highlighting the linguistic, legal, and cultural challenges that arise in this specialized field. Legal translation requires not only a high level of linguistic proficiency but also a deep understanding of legal systems, terminology, and the principles underlying international law. Treaties often contain highly formalized language, ambiguous expressions, and concepts that may not have direct equivalents in other legal systems, making accurate translation particularly difficult.